How to be a Roman soldier - Macdonald, Fiona; Hewetson, N. J. (Washington, D.C. : National Geographic, 2008)
Contains an introduction to what it was like to be a Roman soldier, in simple text with illustrations, including information on armor, weapons, skills, and duties.
Includes bibliographical references (p. 32) and index.
6.2
3-6
3-6
School Library Journal
Horn Book
Keywords: Rome -- Army -- Juvenile literature; Soldiers -- Rome -- Juvenile literature; Rome -- History, Military -- 30 B.C.-476 A.D. -- Juvenile literature; Rome -- Military antiquities -- Juvenile literature; Rome -- Army; Soldiers; Rome -- History; Rome -- Army; Soldier; Rome -- History